Recognition of a human sperm surface protein involved in the progesterone-initiated acrosome reaction by antisera against an endomembrane progesterone binding protein from porcine liver - Buddhikot, Madhavee; Falkenstein, Elisabeth; Wehling, Martin; Meizel, Stanley (Molecular and cellular endocrinology, 1999)
Antisera against a porcine liver endomembrane progesterone (P4)-binding protein inhibited the P4-initiated acrosome reaction (AR) but not the ionomycin-initiated AR of human sperm. Indirect immunofluorescence studies detected antigen in the sperm head that moved during capacitation from a posterior head region to a midhead region. Moreover, the antisera detected a 44.6 kDa protein in western blots of sperm digitonin extracts. These results suggest that a sperm protein with at least partial homology to the liver endomembrane P4-binding protein, is a putative P4-receptor on the sperm plasma membrane involved in the P4-initiated AR.